Use of a Smartphone Medication Reminder Application to Support Emerging Adult Adherence to Non-Antibiotic Treatment for Viral Upper Respiratory Tract Infection. (October 2022) - Brinker, David L.; Foley, Kasey A.; Zhou, Yanmengqian; Acevedo-Callejas, Michelle; Li, Yuwei; Farrell, Erina L.
Objective: This research study is a test of the efficacy of a smartphone-installed medication reminder application to support provider-recommended treatment plans for young adult patients who were seen for upper respiratory tract infections (URTIs) and were not prescribed an antibiotic. Methods: Two hundred seventy-five patients seen at a university student health center for URTI symptoms were randomly assigned to the medication reminder app intervention or a control group and then surveyed both 1 and 14 days after their medical visits with questions about the treatment plan, their satisfaction with medical care, and the electronic support tools. Results: Compared to the control condition, patients using the reminder app reported more adherence to provider-recommended treatment plans. Patients with lower social support availability benefited more from being provided with these tools. Conclusion: These findings suggest that medication reminder apps have utility for increasing patient adherence to non-antibiotic URTI treatment plans, particularly among patients who lack high-quality informational and tangible social support. Innovation: This study demonstrates innovation in use of the medication reminder app to promote antibiotic stewardship with young adult patients in primary care.